2014
DOI: 10.11648/j.cmr.20140304.15
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Beliefs and Obstacles as Limitations in Promoting Exclusive Breastfeeding among Working Class Mothers Attending Infant Welfare Clinic at University of Nigeria Teaching Hospital (UNTH), Enugu State

Abstract: Objective: The research was designed to ascertain information on the mothers' beliefs and obstacles as limitations in promoting exclusive breastfeeding among the working class mothers aimed to: (1) to determine the rate of promotion of the awareness on the benefits of exclusive breastfeeding, (2) to determine the obstacles or barriers to the practice of exclusive breastfeeding, (3) to determine the percentage level of working class who practice exclusive breastfeeding, (4) to assess the nutritional knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Afrose et al showed that most working mothers who received their main source of information from nurses and other health workers (75 %) were not EBF. Data from work done by Anyanwu and Maduforo in 2004 [28] in a neighboring country, and others [29] concur that the main source of education about breastfeeding provided to working mothers is the health worker, although determinants of EBF among working mothers include the women’s educational status and working conditions [30, 31]. Februhartanty and colleagues presented data similar to those of the current study [30].…”
Section: Discussionsupporting
confidence: 77%
“…Afrose et al showed that most working mothers who received their main source of information from nurses and other health workers (75 %) were not EBF. Data from work done by Anyanwu and Maduforo in 2004 [28] in a neighboring country, and others [29] concur that the main source of education about breastfeeding provided to working mothers is the health worker, although determinants of EBF among working mothers include the women’s educational status and working conditions [30, 31]. Februhartanty and colleagues presented data similar to those of the current study [30].…”
Section: Discussionsupporting
confidence: 77%
“…The health workers are also the main human resources who disseminate information about breastfeeding and their breastfeeding practices could be the ideal behaviour which many other women in the community would like to follow. 5,6 Moreover, hospital professionals are more likely to disseminate their knowledge and practices to others successfully if they themselves could follow recommended breastfeeding practices. However, breastfeeding practices of a these women are likely to be modified by the facilities and support that they receive at the hospital which in the present context is suboptimal in almost all hospitals of Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited acknowledgement of working mothers in the National Policy on Infant and Young Child Feeding in Nigeria (2010), the policy advocates for the provision of an enabling environment which promotes breastfeeding space within the workplace (FMoH, 2010, p. 4). However, working mothers in Nigeria lack breastfeeding space at their workplace (Okwy-Nweke et al, 2014) attributable to the lack of penalty for defaulters -that is the employers (ILO, 2012). Hence, like mothers in Pakistan, working mothers in Nigeria have to travel a considerably long distance to the crèche to nurse the infant (Zafar & Bustamante-Gavino, 2008).…”
Section: Breastfeeding Space and Facilitiesmentioning
confidence: 99%